Ministry Of Tourism Decree No. 120/2014 Amending The Executive Regulations Promulgated By The Minister Of Tourism Decree No. 209 Of The Year 2009 = قرار وزير السياحة رقم 120لسنة 2014 بتعديل القرار 63 لسنة 2014 المعدل للقرار رقم 209 لسنة 2009 بشأن تنظيم الشركات السياحية - Egypt; The middle east library for economic services, translator. (2025)
ministry of tourism decree no. 120 of the year 2014 issued on 5/2/2014 وزارة السياحة قرار رقم 120 لسنة 2014 صادر بتاريخ 5/2/2014